2020
DOI: 10.22161/ijeab.52.15
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of exogenous melatonin on growth, photosynthesis and antioxidant defence system in two Brassica napus L.cultivars under chromium stress

Abstract: Rapid industrialization throughout the world during last few decades causing high chromium resulted widespread of agricultural soil contamination. The increased chromium contents beyond permissible level in some agricultural land areas increasing widespread concern about food safety.This study was carried out for evaluation of metal toxicity damage and its possible mitigation and improved photosynthetic efficiency by melatonin treatment in canola plants exposed to four melatonin levels (0,1,5,10µM) treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…Under severe environmental perturbations, chlorophyll fluorescence is extensively implied to enumerate stress tolerance and acclimation in plants [ 72 ]. During the present study, a significant decrease was observed in the Fv/Fm, ΦPSII, and qP under Cr stress, and these results are consistent with those reported in Wheat [ 73 ], Tomato, and Brassica napas [ 39 ]. Impaired PSII electron flow under Cr stress can cause photo-inhibition that enhances the obliteration in antenna molecules [ 74 , 75 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Under severe environmental perturbations, chlorophyll fluorescence is extensively implied to enumerate stress tolerance and acclimation in plants [ 72 ]. During the present study, a significant decrease was observed in the Fv/Fm, ΦPSII, and qP under Cr stress, and these results are consistent with those reported in Wheat [ 73 ], Tomato, and Brassica napas [ 39 ]. Impaired PSII electron flow under Cr stress can cause photo-inhibition that enhances the obliteration in antenna molecules [ 74 , 75 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results, several recent studies have also documented a decline in growth and biomass in different plants such as Brassicca napus , wheat, and Arabidopsis under Cr stress [ 35 , 36 , 37 ]. The reduction in plant growth by Cr phyto-toxicity has been suggested to result from the degradation of chlorophyll pigments [ 38 , 39 ], disturbed nutrient uptake balance [ 33 ], ROS overproduction, destruction of cellular ultrastructure [ 40 ], and disorganization in antioxidant defense machinery [ 33 ]. Hence, it is a prerequisite to improve the Cr stress tolerance in faba bean to avoid its negative effect on plant growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, MT treatment increased Bermuda grass’ resistance to Pb stress [ 95 ]. External MT treatment to Brassica napus (canola) enhanced growth traits under Cr stress through higher PS II efficiency and photosynthetic quotient (PQ) redox rate [ 85 ]. Application of MT in Cr-stressed Origanum majorana plants preserved higher levels of photosynthetic pigments and less ROS by stimulating the antioxidant machinery and osmotic balance, decreased lipid peroxidation, and improved cellular membrane integrity [ 77 ].…”
Section: Role Of Exogenous Melatonin On Heavy Metal Stress Tolerancementioning
confidence: 99%
“…Pers.) [128] maize (Z. mays L.) [120] Ulva (green macroalga) [141] Cd mallow (Malva parviflora, Malvaceae) [49] Spinacia oleracea L. [142] strawberries (Fragaria × ananassa) [81] alfalfa [130] tomato [131][132][133] wheat [124,134] Cyphomandra betacea [135] Malachium aquaticum [136] Galinsoga parviflora [136] Perilla frutescens [137] rice [138,139] Ulva [140,141] rapeseed (Brassica napus) [48] cucumber (Cucumis sativus L.) [95] Cu cucumber (Cucumis sativus L.) [100] melon (Cucumis melo L.) [45] Zn Ulva (green macroalga) [141] wheat (Triticum aestivum L.) [143] safflower (Carthamus tinctorius L.) [53] Al soybean (Glycine max L.) [148] wheat [149] rapeseed (Brassica napus) [48] V watermelon (Citrullus lanatus) [50] Ni tomato (S. lycopersicum L.) [144] Cr wheat (Triticum aestivum L.) [145] canola (Brassica napus L.) [147] B wheat (Triticum aestivum ) [30] As rosemary (Rosmarinus officinalis L.) [150] rice (Oryza sativa L.) [41,51] AsA-GSH cycle Pb bermudagrass (Cynodon dactylon L.) [128] maize (Z. mays L.) [120] Ulva (green macroalga)…”
Section: Plant Specie Referencesmentioning
confidence: 99%